Dakwah Irsyad: Paradigma Dakwah Bimbingan Konseling Islam - Fadila Elma Ramadhani; Umi Halwati (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2024)
Da'wah irsyad represents a specific form of da'wah that places particular emphasis on the provision of spiritual guidance and direction. It plays a pivotal role in the formation of a society that is based on Islamic moral and ethical values. The objective of irsyad da'wah is to facilitate a comprehensive understanding of religious teachings, encompassing not only intellectual comprehension but also the capacity to apply these teachings in one's daily life. This research project aims to explore the paradigm of irsyad da'wah, which represents the paradigm of da'wah in Islamic counselling guidance. This research is qualitative in nature, employing a library research method to explore the existing literature on the subject matter and to contribute to the accumulation of scientific knowledge in the field of da'wah and Islamic counselling guidance. The findings of this study indicate that irsyad da'wah is a crucial element in the development of an individual Muslim's mental, spiritual, and moral wellbeing. It has the potential to enhance the quality and solemnity of The implementation of Irsyad da'wah facilitates the worship of every Muslim in accordance with Islamic law. This, in turn, contributes to the improvement of social conditions in society at large. The early mental and spiritual development of individuals can prevent the emergence of various social problems in Muslim society. The method of irsyad da'wah encompasses the following techniques: khitobah (discourse), daras (teaching), tamsil (parable), uswah shalihah (exemplary good behaviour), and kitabah (writing). It is implemented through education in schools and services.